Stakeholder perceptions of forest disturbance drivers and management responses are aligned in Central Europe - Michaela Perunová; Roman Modlinger; Vilém Jarský; Tomáš Hlásny (Ambio, 2026)
Forest disturbances are increasingly understood as social-ecological phenomena involving diverse actors. Here, we focused on one of the Europe’s largest recent disturbances—the drought-triggered bark beetle outbreak in Central Europe (2017–2022). Based on a survey of 165 respondents, we examined perceived disturbance drivers, response actions, and the alignment between them as an indicator of a value-action gap that is often present in social-ecological and governance systems. Climatic and forest structure-related factors were identified as the dominant drivers, aligning with current scientific understanding, whereas socio-economic and management constraints were perceived as less influential. Reported responses reflected awareness of climate-change risks and involved workforce training, adaptive change in species composition, and water-retention measures. Cause–action alignment was observed in nearly half of respondents, particularly among managers and legal entities. We found a relatively sound understanding of disturbance causes and corresponding responses, likely shaped by recent experience with an unprecedented disturbance impact.